2022
DOI: 10.1002/art.42017
|View full text |Cite
|
Sign up to set email alerts
|

Defibrotide Inhibits Antiphospholipid Antibody–Mediated Neutrophil Extracellular Trap Formation and Venous Thrombosis

Abstract: Objective. Defibrotide is a heterogenous mixture of polyanionic oligonucleotides currently approved for treatment of transplant-associated venoocclusive disease. While defibrotide has a known role in limiting endothelial cell activation, some studies have also demonstrated anti-leukocyte properties. In a recent study, we found that neutrophil extracellular traps (NETs) play a role in the thrombotic complications of antiphospholipid syndrome (APS). In the present study, we investigated the hypothesis that defib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…Once the anti-β2GPI response is started, aPL can react with β2GPI on neutrophils as described ( 13 , 15 , 47 ). This may activate neutrophils directly, boost inflammation and force neutrophils to act as antigen-presenting cells via MHC II-mediated pathways, further stimulating the adaptive response against β2GPI ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once the anti-β2GPI response is started, aPL can react with β2GPI on neutrophils as described ( 13 , 15 , 47 ). This may activate neutrophils directly, boost inflammation and force neutrophils to act as antigen-presenting cells via MHC II-mediated pathways, further stimulating the adaptive response against β2GPI ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…As such it could represent a target antigen recognized by anti-b2GPI antibodies. The interaction of the aPL with the b2GPI at the neutrophil membrane could determine an activation signal, stimulating and amplifying the generation of NETs (13,15,47) One model of fetal loss induced by the passive infusion of very high amounts of aPL raised the potential role of neutrophil recruitment and activation by C5a and/or Tumor Necrosis Factor (TNF) in aPL-mediated placenta damage (48). This finding may suggest increased NETosis which in turn can contribute to damage of trophoblast, decidual and endothelial cells.…”
Section: Neutrophils Nets and Apsmentioning
confidence: 99%
See 1 more Smart Citation
“…NETs are large, extracellular, web-like structures composed of DNA fibers coated with histones and granule proteins. Various stimuli trigger NET formation, such as lipopolysaccharides (LPS), phorbol 12-myristate 13-acetate (PMA) ( 5 ), high mobility group box 1 [HMGB1] ( 21 ), tumor-associated stimuli (tumor-associated antigen, granulocyte-colony stimulating factor [G-CSF] ( 22 ), C-X-C motif chemokine ligands [CXCLs] ( 23 ), cathepsin C ( 24 ), amyloid β ( 18 ), tissue inhibitor of metalloproteinases-1 [TIMP1] ( 16 )), different immunological stimuli (interleukin [IL]-8/CXCL8, interferon [IFN]-α/IFN-γ/C5a, granulocyte-macrophage [GM-CSF/C5a), IL-1β, IL-17, IL-18, IL-33, immune complex ( 5 , 20 , 25 30 ), and other pathogen-associated molecular pattern molecules(PAMPs) ( 31 , 32 ), autoantibodies ( 33 ), activated platelets ( 34 ), bacteria ( 35 , 36 ), viruses ( 37 ), fungi, calcium ionophores ( 38 ), cigarette smoke ( 39 ), free fatty acids ( 40 ), and bleomyci ( 41 ) ( Table 1 ). These stimuli activate the cell surface receptors of neutrophils; for example, HMGB1 recognizes advanced glycation end products (RAGE) receptor and toll-like receptor 4 (TLR4) ( 42 ), C3a recognizes C3a receptor (C3aR) ( 43 ), C5a recognizes C5a receptor (C5aR) ( 44 ), CXC chemokines recognize CXC chemokine receptors (CXCRs) ( 23 ), immune complex activate the FcγRIIIb receptor ( 45 ), LPS and platelets activate the toll-like receptor (TLR) ( 46 , 47 ), bacterial products recognize G protein-coupled receptors ( 48 ), fungi recognize the Dectin1 and Dectin 2 receptor ( 49 , 50 ).…”
Section: Net Structure and Formationmentioning
confidence: 99%
“…Successful approaches have included neutrophil depletion, deoxyribonuclease administration (dissolves NETs), activation of neutrophil surface adenosine receptors, and administration of phosphodiesterase inhibitors [70–72]. A recent study put forth the idea that the polyanionic compound defibrotide (first reported as a potential therapy for CAPS some 20 years ago [73]) has a protective role in part through inhibition of NET release [74 ▪ ].…”
Section: Neutrophils and Neutrophil Extracellular Trapsmentioning
confidence: 99%